(untitled) (Jurnal Bina Praja, 2020)
The phenomenon of the "Golput" occurs in each election fluctuation, sometimes up and down, sometimes influenced by various factors. This research uses the literature study method by summarizing some documentation related to Indonesia’s phenomenon of abstentions. Factors that cause voters not to give their voting rights are political, ideological, and identity factors. But abstentions can also be influenced by an improperly organized election system. From the results of this study, someone behaves abstentions from the technical aspects due to voters’ technical constraints. It prevents them from exercising their right to vote, for example, having other activities at the same time on election day so they cannot come to the voting place. Golput is a person’s attachment to voting in the general election process based on psychological factors, sociological factors, and rational voter factors. On the political aspect, abstentions have reasons such as distrust of the party, and candidates do not believe in a better chance. Meanwhile, if viewed from one aspect, identity can see based on religion, education level, age, gender, etc. In terms of faith, a person decides to abstain because party is expected not to be elected as a candidate. For example, Christian tends not to choose a party that carries Islam, such as the Prosperous Justice Party (PKS), the United Development Party (PPP), and others. In contrast, most nationalist candidates or political parties are considered less representative to accommodate their aspirations. Then abstentions will be the final choice taken.